The micturition switch and its forebrain influences. (16th November 2012) - Griffiths, D. J.; Fowler, C. J.
Abstract Dr DeGroat and Wickens has reviewed the central neural mechanisms controlling the lower urinary tract with a major focus on the brain stem circuitry that mediates the switch‐like characteristics of micturition, in particular the periaqueductal grey and the pontine micturition centre (de 2012). The review culminates in a computer model of how the brainstem switch operates in animals in which forebrain influences on micturition have been removed by decerebration. In this complementary paper, we review the mechanisms of forebrain involvement in the voluntary control of human micturition and the maintenance of continence with evidence based heavily on the results of functional brain imaging experiments.